Pendidikan Kesehatan pada Ibu Hamil tentang Anemia menggunakan Media Video di Kota Palangka Raya - Oktaviani Oktaviani; Heti Ira Ayue (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
In developing countries with high levels of morbidity in pregnant women, anemia is a significant health problem and is one of the risk factors for postpartum bleeding. One area with low Fe intake data in Palangka Raya City is Puskemas Jekan Raya. In pregnant women, the intake of Fe is low and thus should be suspected as an indication of the anemia triggering factor during pregnancy. Efforts to increase pregnant women's knowledge of anemia can be made through improving healthcare employees with information or health education; particularly video media consist of a combination of images and sounds. Three methods have been applied in the Community Service Activity Method, including the preparation, implementation of activities, and evaluation. The activity was carried out at the Puskemas Pembantu Bumi Palangka, Jekan Raya District, Palangka Raya City, using a class meeting of pregnant women. Media or aids used in performing these activities, such as paperwork, laptops, projectors, and videos on anemia prevention in pregnant women. This activity increases pregnant women's knowledge by 80%. In addition, pregnant women's classroom activities are also very beneficial because they improve interaction and share information.